Comparing the effect of two different exercise types, mini-trampoline and fast-walking to gastrocnemius/soleus muscle elasticity by sonoelastrography - Koca, Tuba Tülay; Baykara, Murat; Demirel, Adnan; Berk, Ejder (The European Research Journal, 2019)
Objectives: Sonoelastography is a newly introduced ultrasound technique that evaluates tissue elasticity and thus provides additional information to that offered by conventional ultrasound images. Here, we compared the effect of ballistic jumping on mini-trampolin with walk exercise to the elasticity of gastrocnemius/soleus muscles with quantitative measurements by sonoelastography. Methods: Forty volunteer healty male cases between the ages of 20-22 years were included the study. Initially, both exercise groups were subjected to joint warm-up movements for 8 minutes. Twenty of the cases (40 legs) had mini-trampoline (balistic jumping) exercise for 15 minutes. Another 20 cases (40 legs) had 15 minutes fast-walk exercise. Measurements were made immediately before and after the procedure (within 5 minutes) with the sonoelastography. Results: A statistically significant difference was observed in the gastrocnemius/soleus muscles after exercise in the trampoline group according to sonoelastography strain value (SESV) data separately (p = 0.0001 / p = 0.0001). According to this, when the SESV values evaluated after 15 minutes of jump with the trampoline, we obtained that the elasticity increases and stifness decreases in the calf muscles. In the walking group, no statistically difference was observed in the gastrocnemius/soleus muscles after exercise separately (p = 0.7925 / p = 0.1879). Conclusions: According to the study, in the trampoline group in general, a decrease in strain values and an increase in elasticityin muscle groups were found; in the walking group, a decrease in muscle elasticity, an increase in stiffness and muscle strain were found eventually. We found that the 15-minutes exercise program on the mini-trampoline is more effective as a heating technique and has more positive effect on muscle elasticity than the 15-minutes walking exercise.